Use of Bedside Ultrasound to Assess Muscle Changes in the Critically Ill Surgical Patient. Issue 2 (11th May 2020) - Bury, Christan; DeChicco, Robert; Nowak, Diane; Lopez, Rocio; He, Lulu; Jacob, Sandhya; Kirby, Donald F.; Rahman, Nadeem; Cresci, Gail
Abstract: Background: Critical illness causes hypercatabolism, loss of lean body mass (LBM), and poor outcomes. Evaluating LBM in the critically ill is challenging, and it is uncertain whether nutrition support (NS) impacts LBM. This study measured quadriceps muscle layer thickness (QMLT) by bedside ultrasound (US) to estimate LBM changes in surgical intensive care unit (SICU) patients and healthy controls (HCs). Methods: Trained RDNs measured QMLT via US at the midpoint and one‐third distance between the superior margin of the patella and the anterior superior iliac spine. QMLT measurements were taken upon enrollment and repeated 1–2 times over 10 days. Results: Fifty‐two SICU patients and 15 HCs were enrolled. Average SICU percent QMLT loss per day at the midpoint and one‐third landmarks was 3.2 ± 3.8 ( P < 0.001) and 2.9 ± 5.7 ( P = 0.001); and QMLT loss was higher between the second and third measurements (4.0 ± 8.0, P = 0.005 and 4.3 ± 9.8, P = 0.017 at the midpoint and one‐third landmarks) compared with that at the first and second measurements (1.7 ± 9.2, P = 0.20 & 1.7 ± 9.4, P = 0.22). Changes were not associated with NS received. No significant QMLT change was found in HCs. Conclusions: SICU patients significantly lost QMLT over 10 days, with greater losses occurring after 5 days. These results support RDNs performing USs to detect QMLT changes and suggest this technique could be valuable to evaluate LBM changes in critically ill patients.